Cybersecurity Training to Improve Student Awareness and Skills - Muhammad Mushfi El Iq; Ghufron Jailani; Moh. Roikul Hasan; Moh. Khozinul Ajaib (Dedikasi Sosial: Jurnal Pengabdian Masyarakat, 2025)
Along with technological advances in the digital era, cybersecurity has become a serious challenge faced by various groups, including Islamic boarding schools. As young generations actively engage with social media, digital applications, and online services, santri are vulnerable to cyber threats such as phishing, malware, and identity theft. The low levels of digital literacy and cybersecurity technical skills make this group urgently in need of specialized training. This community service program aims to improve santri's awareness and skills in recognizing, preventing, and responding to cyber threats. The method applied was a participatory training approach that included interactive lectures, group discussions, real-life threat simulations, and hands-on practice with digital security technologies. The training results indicated significant improvement in santri's understanding and skills in cybersecurity, as evidenced by pre- and posttest score comparisons and increased confidence in addressing potential threats. In addition, a cyber-aware community was established within the pesantren environment, serving as agents of change in disseminating knowledge and skills to other santri. In conclusion, this training not only enhanced santri's digital literacy but also contributed to the development of a stronger culture of cybersecurity in the pesantren environment. In the future, similar activities are recommended to be developed continuously and expanded in scope to achieve broader benefits.